The Role of The Principal's Leadership to Improve Student Achievement at SMAN 1 Bababakan - Adha, Mohamad (IAIN Syekh Nurjati Cirebon, 2021)
THE ROLE OF THE PRINCIPAL'S LEADERSHIP TO IMPROVESTUDENT ACHIEVEMENT AT SMAN 1 BABAKAN, CIREBON REGENCYÂ ABSTRACTThe success of schools in achieving achievements is the duty and responsibility of all parties, but the most important thing is how the principal as a leader manages effectively and efficiently. Research purposes This study aims to describe the role of the principal's leadership in improving student achievement at the State Senior High School 1 Babakan, Cirebon Regency. The type of thesis research is qualitative research with a descriptive approach, the methods used are in-depth interviews, observation and documentation. Data analysis starts from data collection, data reduction, data presentation and drawing conclusions. The results showed that the principal's leadership performance carried out programs such as increasing professionalism, monitoring and evaluating teaching and learning activities, disseminating the school's vision and mission, and coordinating. Student learning achievement in the academic field still tends to fluctuate and there is a need for further improvement, while for non-academic achievements it can be said to be good by achieving many achievements. The principal's leadership role in improving student achievement includes roles as educator, manager, administrator, supervisor, leader, innovator and motivator. In general, the principal has carried out his role well in an effort to improve student achievement and students can achieve achievements from the programs that have been run by the school.Keywords : Leadership, Principal, Student Achievement.PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKANPRESTASI SISWA DI SMAN 1 BABAKAN KABUPATEN CIREBONÂ ABSTRAKSetiap sekolah tentunya memiliki tata usaha di dalamnya yang bertugas untuk melakukan kegiatan administrasi sekolah termaksud dalam kegiatan kearsipan. Namun dalam hal ini banyak sekali lembaga yang kurang memperhatikan kearsipan tidak terkecuali sekolah. Dalam hal ini tata usaha sangatlah perlu mengadakan kearsipan disekolah. Arsip sebagai sumber informasi tertulis yang dapat membantu mengingatkan kita kepada informasi-informasi terdahulu. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana tata usaha dalam menjalankan perannya dalam mengelola arsip sekolah dan mengetahui apa saja kendala-kendala yang dialami tata usaha dalam mengelola arsip. Penelitian ini merupakan penelitian kualitatif deskriptif. Teknik pengumpulan data dalam penelitian ini yaitu dengan menggunakan wawancara, observasi, dan dokumentasi. Hasil penelitian ini tata usaha sudah melakukan dengan baik pengelolaan arsip sekolah walau masih terdapat beberapa kekurangan di dalamnya. Berdasarkan hasil penelitian dapat disimpulkan bahwa tata usaha SMK Veteran sudah melaksanakan perannya dengan baik dalam hal mengelola arsip sekolah hanya saja perlu ditingkatkan lagi karena agar dapat lebih mengoptimalkan kegiatan administrasi sekolah.Â Kata Kunci : Tata Usaha, Pengelolaan, Arsip